2014
DOI: 10.14710/jitaa.39.3.152-158
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal Fermentation and Blood Glucose at Low and High Level Intake of Growing and Mature Kacang Goat

Abstract: Tujuan dari penelitian ini adalah untuk membandingkan konsentrasi Volatile Fatty Acids (VFA) rumen dan kadar glukosa darah antara kambing Kacang muda dan dewasa dengan level pakan berbeda. Delapan ekor umur muda (6-7 bulan) dengan bobot badan (BB) 12,75 ± 2,67 kg dan 8 ekor umur dewasa (8-12 bulan) dengan BB 34 ± 3,32 kg. Pakan yang diberikan berupa pakan komplit bentuk pellet dengan kandungan protein kasar (PK) 18,8% dan total digestible nutrients (TDN) 78,82%. Pakan diberikan dalam 2 level yaitu rendah (low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
3
1
0
1
Order By: Relevance
“…The results of this study were similar to the report of Estermann et al (2002) that cattle aged 4, 7 and 10 months had the same ability in digesting feed. Similar result was also reported by Luthfi et al (2014) that goats aged 6 and 12 months had similar ability to digest feed.…”
Section: Feed Intake and Digestibilitysupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study were similar to the report of Estermann et al (2002) that cattle aged 4, 7 and 10 months had the same ability in digesting feed. Similar result was also reported by Luthfi et al (2014) that goats aged 6 and 12 months had similar ability to digest feed.…”
Section: Feed Intake and Digestibilitysupporting
confidence: 90%
“…This was attributed to the fact that ram had higher body weight than the lambs. Animal with higher body weight have greater gut capacity and need more nutrients for maintenance (McDonald et al, 2012;Luthfi et al, 2014).…”
Section: Feed Intake and Digestibilitymentioning
confidence: 99%
“…The dry matter intake (DMI, kg/d and %BW ) was similar among treatments with different roughage sources and protein sources supplementations, the mean dry matter intake (kg/d) in T1 (UTRS+LL), T2 (UTRS+CL), T3 (FNPG+LL) and T4 (FNPG+CL) was 0.63, 0.71, 0.69 and 0.66 respectively (P>0.05). DMI in this study was in agreement with previous report of Luthfi et al (2014) who described that intake level increased DMI (0.50 kg/d) in Kacang goat. Furthermore, when fed goats were fed with FNPG+CL the %BW intake (2.34%) tends to be higher compared to the other treatments, but lower than that reported by Hue et al (2010) who fed guinea grass (Panicum maximum) and cassava chips supplemented with wilted cassava foliage in lambs were the DM intake reported as %BW was 3.6.…”
Section: Total Dry Matter Intake Nutrient and Ruminationsupporting
confidence: 93%
“…Blood glucose value ranged between 53.25 to 60.25 mg/dl according to USDA (2020) the normal blood glucose value for the Goat is 40-60mg/dl. Additionally, this result agrees with Luthfi et al (2014) who fed Kacang goat with high and low intakes level are reported blood glucose of 56.39 to 64.48 mg/dl.…”
Section: Blood Metabolitessupporting
confidence: 91%
“…Hal ini sesuai dengan pendapat Adiwinarti et al (2018) bahwa nilai pH mengalami penurunan karena peningkatan volatile fatty acid (VFA) di dalam rumen. Pada jam ke-3 menuju jam ke-6 setelah makan pH cairan rumen meningkat akibat terjadinya absorbsi VFA pada dinding rumen (Luthfi et al 2014).…”
Section: Konsentrasi Vfa Cairan Rumenunclassified